No supplementary evidence of attention to a spatial cue when saccadic facilitation is absent - Joe MacInnes (Scientific Reports)
Attending a location in space facilitates responses to targets at that location when the time between cue and target is short. Certain types of exogenous cues – such as sudden peripheral onsets – have been described as reflexive and automatic. Recent studies however, have been showing many cases where exogenous cues are less automatic than previously believed and do not always result in facilitation. A lack of the behavioral facilitation, however, does not automatically necessitate a lack of underlying attention to that location. We test exogenous cueing in two experiments where facilitation is and is not likely to be observed with saccadic responses. We also test alternate measures linked to the allocation of attention such as saccadic curvature, microsaccades and pupil size. As expected, we find early facilitation as measured by saccadic reaction time when CTOAs are predictable but not when they are randomized within a block. We find no impact of the cue on microsaccade direction for either experiment, and only a slight dip in the frequency of microsaccades after the cue. We do find that change in pupil size to the cue predicts the magnitude of the validity effect, but only in the experiment where facilitation was observed. In both experiments, we observed a tendency for saccadic curvature to deviate away from the cued location and this was stronger for early CTOAs and toward vertical targets. Overall, we find that only change in pupil size is consistent with observed facilitation. Saccadic curvature is influenced by the onset of the cue, buts its direction is indicative of oculomotor inhibition whether we see RT facilitation or not. Microsaccades were not diagnostic in either experiment. Finally, we see little to no evidence of attention at the cued location in any additional measures when facilitation of saccadic responses is absent.